2020
DOI: 10.1186/s12917-020-02630-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the antibacterial activity of antimicrobial peptide PMAP-37(F34-R) by cholesterol modification

Abstract: Background The problem of increasing resistance against conventional antibiotics has drawn people’s attention. Therefore, the development of novel antibacterial agents with effective and safe therapeutic effects is imminent. Antimicrobial peptides (AMPs) are considered a promising class of antibacterial agents due to their broad antibacterial spectrum. Results In this study, on the basis of our previously studied peptide PMAP-37(F34-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…A previous study demonstrated that pre-incubated PMAP-37(F34-R) in extreme pHs exhibited a stable and maintained antibacterial activity at pH 2-8 and pH 9-11 against S. aureus ATCC 25923 and P. aeruginosa GIM1.551 ( Chen et al, 2020 ). Our results showed that P7 tolerated over a wide range of acidic, neutral even alkaline environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that pre-incubated PMAP-37(F34-R) in extreme pHs exhibited a stable and maintained antibacterial activity at pH 2-8 and pH 9-11 against S. aureus ATCC 25923 and P. aeruginosa GIM1.551 ( Chen et al, 2020 ). Our results showed that P7 tolerated over a wide range of acidic, neutral even alkaline environment.…”
Section: Resultsmentioning
confidence: 99%
“…To determine pH stability, the pH of the peptide’s solution was adjusted to 3, 5, 7, 9, and 11 using 1 M NaOH or 1 M acetic acid (CH 3 COOH). P7 were incubated in the different pH conditions for 1 h, then transferred to inoculated MHB for antibacterial testing ( Chen et al, 2020 ), There was no change of the pH following the addition of peptide. To determine the sensitivity of peptide to proteolytic enzymes, the residual activity of P7 was measured after incubation the peptide with 1 mg/ml (final concentration) of proteolytic enzymes (pepsin or trypsin) at 37°C for 1 h and heat denaturation at 80°C for 1 h. To study thermostability, peptides were pre-incubated without bacteria at various temperatures (40, 60, 80, and 100°C) for 1 h and left to cool for 30 min before testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, our group has performed research on the structural modification and antimicrobial activity of PMAPs. According to the structure and mechanism of PMAPs, many scholars have designed multiple novel modified peptides with increased stability and antimicrobial activity (43)(44)(45)(46)(47)(48)(49)(50). This review mainly summarizes the research progress on the structural characteristics and biological activities of PMAPs in recent years.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Although monomers and dimers show rapid and effective bactericidal activity against most microorganisms, dimeric peptides have a more stable conformation, longer bacteriostatic time, and lower medium sensitivity (34,62). PMAP-37 is an amphiphilic antimicrobial peptide that contains 37 amino acid residues with a molecular weight of 4365.02 Da (38,50), and the amino acid sequence of PMAP-37 is GLLSRLRDFLSDRGRRLGEKIERIGQKIKDLSEFFQS (48,49). PMAP-37 has the highest hydrophobicity and the lowest net charge (22).…”
Section: Porcine Myeloid Antimicrobial Peptidesmentioning
confidence: 99%